A Method of Determining Channeling Parameters in Backscattering Geometry - Kokkoris, M.; Kossionides, S.; Paradellis, T.; Zarkadas, Ch.; Gazis, E. N.; Papadopoulos, C. T.; Vlastou, R.; Aslanoglou, X. (HNPS Advances in Nuclear Physics, 2019)
The energy loss of channeled protons in silicon has been measured in the past in the transmission geometry and was found to be approximately half of the normal loss, thus confirming the equipartition rule. Other measurements however, concerning different crystals (e.g. Ge), deviated from this theory. In the backscattering geometry, the most successful corresponding attempts combined RBS with the nuclear resonance phenomenon. Nevertheless, they involved ether considerable additions to the standard goniometer setup commonly used, or tedious Monte-Carlo calculations, thus limiting their applicability. ïïi the present work, a method for the determination of the energy loss and dechanneling probabilities of axially channeled protons in silicon [100], in the energy range Ep = 1.7-2.6 MeV, is presented. It is carried out in situ, using the same experimental setup and beam properties (size, divergence) with the ones present in the actual analysis of a sample. The results obtained are in good agreement with already existing values in literature.